A global estimate of multiecosystem photosynthesis losses under microplastic pollution - Ruijie Zhu; Zhaoying Zhang; Naichi Zhang; Huan Zhong; Fanqi Zhou; Xiao Zhang; Cun Liu; Yingnan Huang; Yuan Yuan; Yujun Wang; Chengjun Li; Huahong Shi; et al. (Proceedings of the National Academy of Sciences, 2025)
Understanding how ecosystems respond to ubiquitous microplastic (MP) pollution is crucial for ensuring global food security. Here, we conduct a multiecosystem meta-analysis of 3,286 data points and reveal that MP exposure leads to a global reduction in photosynthesis of 7.05 to 12.12% in terrestrial plants, marine algae, and freshwater algae. These reductions align with those estimated by a constructed machine learning model using current MP pollution levels, showing that MP exposure reduces the chlorophyll content of photoautotrophs by 10.96 to 12.84%. Model estimates based on the identified MP-photosynthesis nexus indicate annual global losses of 4.11 to 13.52% (109.73 to 360.87 MT·y −1 ) for main crops and 0.31 to 7.24% (147.52 to 3415.11 MT C·y −1 ) for global aquatic net primary productivity induced by MPs. Under scenarios of efficient plastic mitigation, e.g., a ~13% global reduction in environmental MP levels, the MP-induced photosynthesis losses are estimated to decrease by ~30%, avoiding a global loss of 22.15 to 115.73 MT·y −1 in main crop production and 0.32 to 7.39 MT·y −1 in seafood production. These findings underscore the urgency of integrating plastic mitigation into global hunger and sustainability initiatives.